Officiating speech 8th International Conference on Molecular Biology and Biotechnology / Prof. Ir. Ts. Dr Mohamad Hafiz Mamat Deputy Rector (Research & Innovation) Universiti Teknologi Mara Selangor - Mamat, Mohamad Hafiz (2025)
As we officially open this conference, themed 'Revolutionizing Molecular Biology and Biotechnology with AI: Transforming Data for Impactful Innovation', I encourage everyone to embrace the opportunities to share ideas, build collaborations, and gain new insights from the diverse expertise present.